Female Labor Force Participation and Labor-Saving Gadgets - GUHA, Brishti (Institutional Knowledge at Singapore Management University, 2005)
We show under what conditions women would migrate out of the household sector into formal sector jobs, in response to increased ability to use labour saving household gadgets, which raise the productivity of female labour engaged in household tasks. We model a small open economy with three outputs: one labour-intensive manufactured export (cloth), one capital-intensive intermediate good (gadgets) and one non-traded 'household-sector good' (meals) which requires both female labour and household gadgets for production. A terms-of-trade improvement capturing greater world demand for labour-intensive manufactured exports enables greater adoption of labour-saving household gadgets in response to changing relative prices. If the elasticity of substitution between female labour and household gadgets exceeds a threshold, this will result in women migrating from the household to formal sector employment. What matters is not the actual date of invention of these labour-saving appliances (female labour force participation may not grow significantly until long after) but their increased adoption by the small economy in response to changing relative prices.